PENINGKATAN PENGETAHUAN ORANGTUA DAN PENCEGAHAN GANGGUAN PERNAPASAN TERHADAP ANAK PRASEKOLAH UNTUK MENGOPTIMALKAN KINERJA OTAK ANAK PADA KB BELIA DI DESA NAMBO TAHUN 2024 - Achwan, Achwan; Hariandja, Andy Martahan; Pramesthi, Daffiela Sekar; Suprianto, Dodi; Puspitaningtias, Dzaky Aulia; Cahyaningrum, Farah; Aminurrahman, Fatih; Adelin, Shafira Prajawati; Din Hidayati, Wukir Asih (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2025)
Respiratory system disorders are often suffered by children under 5 years of age due to immature immune systems, so they often attack children whose immunization status is incomplete or children whose immune systems are compromised. Air pollution causes premature deaths globally every year. The impact of air pollution can cause respiratory damage which can lead to decreased lung function. Chest therapy is an important therapy in the treatment of respiratory diseases for children who suffer from respiratory diseases (Nurul Aula, 2020). The aim of this community service is to determine the level of understanding of parents of KB Youth students regarding respiratory disorders and how to prevent them. The method for implementing this community service activity is socialization and identification by interviewing participants, counseling and exercises by demonstrating hand washing techniques, breathing exercises with play therapy and chest therapy for community service participants. Before and after the activity, an evaluation will be carried out in the form of giving a questionnaire to obtain information related to increasing participants' knowledge. There were 54 participants who were mothers of toddlers. The results achieved in this community service were the establishment of cooperation with the Nambo Village Youth Family Planning Center and the participants, the implementation of counseling and education demonstrating hand washing techniques, breathing exercises with play therapy and chest therapy for participants as well as the implementation of community service activity evaluations. Conclusion There is an increase in parental knowledge and how to prevent respiratory disorders in preschool children to optimize children's brain performance in young KB in Nambo village in 2024.